2020
DOI: 10.1159/000508738
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis of the Pharmacogenetics of <b><i>ARMS2</i></b> A69S Polymorphism and the Response to Advanced Age-Related Macular Degeneration

Abstract: Background Age-related macular degeneration (AMD) causes irreversible vision loss, and targeted anti-vascular endothelial growth factor (VEGF) therapy is now the most common and effective treatment. The aim of this meta-analysis is to discuss whether genetic polymorphism of ARMS2 A69S could confer susceptibility to advanced AMD with the response to anti-VEGF treatment. Methods We performed a meta-analysis of relevant published studies selected through electronic databases. A total of 21 preferred studies regar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…ARMS2 rs10490924 is correlated with elevated C-reactive protein levels [ 318 ], suggesting an inflammatory mechanism at play. Interestingly, while the ARMS2 rs10490924 G allele is associated with an increased risk of progression to advanced stages of disease [ 296 ], the G allele is also associated with a higher likelihood of MNV response to anti-VEGF therapy in patients who have progressed to neovascular disease [ 98 , 317 , 319 , 320 , 321 , 322 ], particularly in East Asian populations [ 321 ]. A similar correlation has been demonstrated between HTRA1 rs11200638 and increased likelihood of response to anti-VEGF therapy [ 317 ].…”
Section: Genes Implicated In Multiple Pathwaysmentioning
confidence: 99%
“…ARMS2 rs10490924 is correlated with elevated C-reactive protein levels [ 318 ], suggesting an inflammatory mechanism at play. Interestingly, while the ARMS2 rs10490924 G allele is associated with an increased risk of progression to advanced stages of disease [ 296 ], the G allele is also associated with a higher likelihood of MNV response to anti-VEGF therapy in patients who have progressed to neovascular disease [ 98 , 317 , 319 , 320 , 321 , 322 ], particularly in East Asian populations [ 321 ]. A similar correlation has been demonstrated between HTRA1 rs11200638 and increased likelihood of response to anti-VEGF therapy [ 317 ].…”
Section: Genes Implicated In Multiple Pathwaysmentioning
confidence: 99%
“…This may be linked to ethnic variations, with subgroup analyses in both papers finding the relationship occurring in Caucasian populations and not East Asians, however it may be due to the significantly lower incidence rates of CFH polymorphisms in Asians and the limited number of Asian studies included. On the other hand, two meta-analyses of studies investigating polymorphisms of ARMS2 have found that the minor allele of A69S was associated better treatment responses to anti-VEGF among East Asians; 71 , 72 though not all studies included used visual acuity to define treatment response. For HTRA1 gene, a meta-analysis of five studies found no associations between its polymorphisms and treatment response.…”
Section: Patient Characteristicsmentioning
confidence: 99%
“…The rs10490924/A69S polymorphism, which surrounds two genes, ARMS2 and HTRA1, has been reproducibly observed as a strong genetic risk factor for AMD [ 46 , 47 ]. Although the mechanism causing the disease susceptibility is not fully clear, ARMS2 A69S polymorphism influences the anti-VEGF response in late-stage AMD, notably in the East Asian population [ 48 ], suggesting that the latter mutation may serve as a prognostic factor for the anti-VEGF response, especially in A-allele carriers or the AA genotype, whose detection may be an indication for early intervention [ 49 ]. Other reports identified the regulatory region HTRA1 rs11200638 [ 50 , 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…Similarly to CFH, CFI rs2285714 is shown to respond worse to antiangiogenic treatment [ 141 ]. ARMS2 A69S is a prognostic factor for an anti-VEGF response in wet AMD in the East Asian population, but not in the Caucasian or Middle Eastern group [ 48 ]. HTRA1-rs11200638 SNPs suggested an improvement in VA for patients with the variated genotype [ 142 ].…”
Section: Resultsmentioning
confidence: 99%